Dignity Takings in Gangland’s Suburban Frontier - Yuille, Lua Kamál (2018)
This paper engages the evolving dignity takings framework, first developed by Bernadette Atuahene, in the context of contemporary American street gangs (e.g. Crips, Bloods, Latin Kings, etc.). Contrary to most popular accounts, it starts with a reimagined and complicated notion of street gangs that emphasizes not their secondary or tertiary violence and criminality but their primary function as corporate institutions engaged in the sustained, transgressive creation of alternative markets for the creation of the types of property interests that scholars have associated with the development and pursuit of identity and “personhood.” From this perspective, the paper applies the dignity takings analysis to public nuisance abatement actions (commonly known as gang injunctions), which have become standard tools in the national gang strategy. These civil mechanisms enjoin the conduct and activities of the gangs, prohibiting named individuals from engaging in a panoply of otherwise legal activities: e.g. displaying gang symbols, wearing clothing or colors associated with a gang, possessing tools or objects capable of defacing real or personal property (e.g. pens), and appearing in public view with a known gang member. Through qualitative analyses of interviews, court documents, and political hearings, the paper demonstrates that the dispossession of identity property associated with suburban gang injunctions depresses self-esteem, erodes self-confidence, damages identity and feelings of community worth, and dehumanizes enjoined individuals in a way that deprives them of their fundamental right of dignity, constituting a clear example of a dignity taking